Characterization of convergent thickening, a major convergence force producing morphogenic movement in amphibians - Shook, David R; Wen, Jason WH; Rolo, Ana; O'Hanlon, Michael; Francica, Brian; Dobbins, Destiny; Skoglund, Paul; DeSimone, Douglas W; Winklbauer, Rudolf; Keller, Ray E (eLife, 2022)
The morphogenic process of convergent thickening (CT) was originally described as the mediolateral convergence and radial thickening of the explanted ventral involuting marginal zone (IMZ) of Xenopus gastrulae (Keller and Danilchik, 1988). Here, we show that CT is expressed in all sectors of the pre-involution IMZ, which transitions to expressing convergent extension (CE) after involution. CT occurs without CE and drives symmetric blastopore closure in ventralized embryos. Assays of tissue affinity and tissue surface tension measurements suggest CT is driven by increased interfacial tension between the deep IMZ and the overlying epithelium. The resulting minimization of deep IMZ surface area drives a tendency to shorten the mediolateral (circumblastoporal) aspect of the IMZ, thereby generating tensile force contributing to blastopore closure (Shook et al., 2018). These results establish CT as an independent force-generating process of evolutionary significance and provide the first clear example of an oriented, tensile force generated by an isotropic, Holtfreterian/Steinbergian tissue affinity change.
Keywords: morphogenesis; blastopore closure; biomechanics; gastrulation; convergent thickening; tissue surface tension